Thailand : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Thailand. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses recent developments, outlook and risk, and policies required for a long-lasting recovery of Thailand's economy. Thailand remains resilient in the face of external and internal challenges. However, political uncertainty and structural bottlenecks cloud long-term prospects. The economy recovered in 2015 after a slowdown induced by political uncertainty. Public investment supported economic activity, particularly through community-based infrastructure projects. Monetary policy was eased in the face of below-target inflation. The credit cycle moderated, but household debt reached a historic high. Implementing high-quality fiscal stimulus, easing monetary policy, and safeguarding financial sector stability can strengthen long-term sustainability, equity, and efficiency of Thailand's economy.